(untitled) (Journal of the College of Basic Education, 2022)
The song expressed societies and their artistic and literary values ​​in most countries of the worlddespite class, economic, cultural and other differences; And it became the most popular song templatePopularity and importance among the musical and lyrical forms has gained a wide range of masses loverecipients; Because of the flexibility of the artistic form of the song in adding, deleting or repeating someits parts; According to the visions of the composers and commensurate with the objective and functional conditionsAnd the potential of composers, poets and even singers. The musical introduction is the most important partThis template has an active role in highlighting the composer’s abilities to compose and employ musicThe melody in supplying the word and expressing the poetic meanings and images in it;